Leveraging patents financially : A company perspective - Vries, Dominic (Gabler Verlag, 2012)
Intangible assets such as patents have become important competitive factors and key elements in the value structure of technology-intensive companies. While patents represent the technological capital to a large extent, they are not adequately represented in the field of corporate financing. Based on expert interviews and a large-scale survey, Dominic de Vries provides one of the first in-depth empirical studies into how patents contribute to companies' access to external financial sources. He identifies and analyses the actual extent and influence factors of financial patent utilization across company size clusters and patent-intensive industry sectors in Germany.